Synthesis of a Regulator for UAV Motion Control System under Uncertainty - Sushchenko, Olha; Yakubovskyi , Nazar (Electronics and Control Systems, 2026)
This article represents the study of uncertainties inherent in motion control systems for unmanned aerial vehicles. Both external and internal disturbances acting on moving objects are considered. Expressions for the turbulent wind are given. The analysis of structured and non-structured uncertainties is presented. Results of studying different types of regulators are given, including PID regulators, LQR regulators, robust regulators, and regulators based on non-linear approaches and artificial intelligence methods. The procedure of H infinity synthesis is described. The block diagram of the conversion a continuous regulator in discrete one is represented. The comparative analysis of application LQR and H infinity regulators in loops of tracking by a given trajectory for conditions of the normal and disturbed atmosphere is given. The appropriate graphical dependencies are shown. The obtained results can be useful for aerial objects of a wide class.